German Heart Surgery Report 2020: The Annual Updated Registry of the German Society for Thoracic and Cardiovascular Surgery - Beckmann, Andreas; Meyer, Renate; Lewandowski, Jana; Markewitz, Andreas; Gummert, Jan (The Thoracic and Cardiovascular Surgeon, 2021)
Based on a longtime voluntary registry, founded by the German Society for Thoracic and Cardiovascular Surgery (GSTCVS) in 1980, well-defined data of all cardiac, thoracic and vascular surgery procedures performed in 78 German heart surgery departments during the year 2020 are analyzed. Under the more than extraordinary conditions of the ongoing worldwide coronavirus disease 2019 pandemic, a total of 161,817 procedures were submitted to the registry. A total of 92,809 of these operations are summarized as heart surgery procedures in a classical sense. The unadjusted in-hospital survival rate for the 29,444 isolated coronary artery bypass grafting procedures (relationship on-/off-pump 3.6:1) was 97.2%. For the 35,469 isolated heart valve procedures, (17,471 transcatheter interventions included), the survival rate was 96.7%. Concerning short- and long-term circulatory support, a total of 2,852 extracorporeal life support/extracorporeal membrane oxygenation implantations, respectively, 843 assist device implantations (left/right/biventricular assist device, total artificial device), were registered. In 2020, the number of isolated heart transplantations increased to 340, a rise of 2.1% compared with the previous year. The isolated lung transplantations amounted to 291, a decrease of 6.4%.This annually updated registry of the GSTCVS represents voluntary public reporting by accumulating actual information for nearly all heart surgical procedures in Germany, constitutes advancements in heart medicine, and represents a basis for quality management for all participating institutions. In addition, the registry demonstrates that the provision of cardiac surgery in Germany is up to date, appropriate, and nationwide patient treatment is guaranteed all the time.
Keywords: heart valve surgery; congenital heart disease; coronary artery bypass grafting; aortic surgery; transplantations; heart-lung; COVID-19